Molecular isolation and analysis of the erect wing locus in Drosophila melanogaster. - Fleming, R J (1989)
The molecular study of the erect wing (ewg) locus was initiated by isolating DNA in the 1A8-1B1 interval of the X chromosome. Previous developmental genetic analyses of the mutant alleles at the ewg locus have demonstrated that the wild-type ewg product is essential during embryogenesis and is required postembryonically at least for the development of the indirect flight muscle. To define the ewg-encoding DNA, chromosomal breakpoints that genetically flank the ewg locus were used. P-element-mediated transformation followed by subsequent rescue of the ewg-lethal alleles has defined a 11.5-kilobase genomic fragment as encoding the ewg locus. Northern blot analysis of transcription from this DNA has revealed a complex pattern of transcription with respect to both size and developmental profile. Tissue distribution of putative ewg transcription was examined by in situ hybridization to 6- to 14-h-old embryonic sections. These sections revealed that the expression of putative ewg messages is limited to the central nervous system-derived structures and not observed within the mesoderm during this developmental stage.